Construction of corrosion resistant and osteogenic multiphase reinforced Titanium/hydroxyapatite nanocomposites prepared by spark plasma sintering. Issue 8 (3rd August 2022) - Shao, Zhenyi; Jiang, Xiaosong; Li, Feng; Zhu, Minhao; Maitz, Manfred F.; Song, Tingfeng
ABSTRACT: Poor corrosion resistance and osseointegration of titanium/hydroxyapatite (Ti/HA) composites or coatings limit their application of long-term implants. In this study, spark plasma sintering was employed to fabricate Ti/HA nanocrystalline composites, in which HA was proposed to improve osseointegration of Ti alloys and surface-functionalized nanocarbons (graphene nanoflakes (GNFs) and carbon nanotubes (CNTs)) were proposed to improve corrosion resistance and osteogenicity of Ti/HA nanocomposites. The microstructures indicated that phase transition of Ti, HA decomposition and chemical reaction occurred during sintering and typical microstructural characteristics such as porosity, dislocations, polycrystalline compounds or secondary compounds were present in the Ti/HA nanocomposites. The electrochemical behavior showed that Ti/HA nanocomposites containing graphenes (0.5 GNFs and 0.4CNT/0.1GNFs) had better corrosion resistance compared to other composites (0.5 CNTs and nonreinforced). The embedded graphene acted as an efficient barrier against ionic diffusion, thus causing an effective shielding against corrosion. In vitro cytocompatibility and osteogenesis evaluation demonstrated that 0.4CNT/0.1GNF-reinforced Ti/HA nanocomposites led to optimal osteoblast adhesion and proliferation, support of osteogenic differentiation and osteogenic activity. In summary, overall, considering the corrosion resistance, cytocompatibility and osteogenesis of the Ti/HA nanocomposites, 0.4CNT/0.1GNF-reinforced Ti/HA nanocomposites had acceptable corrosion resistance and optimal cytocompatibility and osteogenicity, making it a potentially feasible bone implant biomaterial. Graphical Abstract: uf0001